Method for manufacturing separator for lithium secondary battery, separator for lithium secondary battery manufactured thereby, and lithium secondary battery including same

By using core-shell structure fibers composed of β-chitin and vinylidene fluoride-trifluoroethylene copolymer in lithium secondary batteries, the problem of heat shrinkage of lithium secondary battery partitions at high temperatures is solved, and low Resistance and improved cycling performance.

CN119137796APending Publication Date: 2024-12-13LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380036183.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-14
Filing Date
2023-12-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lithium secondary battery separators heat shrink at high temperatures, resulting in a decrease in lithium ion conductivity and an increase in resistance, affecting the cycling performance and safety of the battery.

Method used

The core-shell structure fibers composed of β-chitin and vinylidene fluoride-trifluoroethylene copolymer were prepared by coaxial electrospinning method, and the thermal decomposition point was higher than that of β-chitin. The copolymer is heat treated at the temperature of the melting point to melt and recrystallize the copolymer, and maximize the ferroelectricity of the fibers.

Benefits of technology

The good thermal shrinkage characteristics and low resistance of the fibers in lithium secondary batteries are achieved, the uniform migration of lithium ions and the cycling performance of the battery are improved, and the risk of resistance and thermal runaway is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137796A_ABST
    Figure CN119137796A_ABST
Patent Text Reader

Abstract

The method for manufacturing a non-woven separator for a lithium secondary battery includes: (S1) preparing a first solution in which beta-chitin is dissolved in a first solvent and a second solution in which a vinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) is dissolved in a second solvent; (S2) performing coaxial electrospinning with the first solution as a core solution and with the second solution as a shell solution to produce a nonwoven fabric formed from fibers having a core-shell structure having a core of beta-chitin and a shell of vinylidene fluoride-trifluoroethylene copolymer; and (S3) heat treating the nonwoven fabric at a temperature lower than the thermal decomposition point of the beta-chitin and higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer to melt and recrystallize the vinylidene fluoride-trifluoroethylene copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a separator for a lithium secondary battery, a separator for a lithium secondary battery manufactured thereby, and a lithium secondary battery including the same.

[0002] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0038832, filed on March 24, 2023, and Korean Patent Application No. 10-2023-0182432, filed on December 14, 2023, the disclosures of which are incorporated herein by reference in their entirety. Background Art

[0003] In recent years, energy storage technology has received increasing attention. As the application fields of electrochemical devices expand to include mobile phones, portable cameras, laptop computers and even electric vehicles, efforts to research and develop electrochemical devices have become more and more specific. Electrochemical devices are one of the most prominent areas in this regard, and the development of secondary batteries such as lithium secondary batteries that can be charged and discharged has become the focus of attention.

[0004] For the separator constituting such a battery, its basic requirement is to separate the positive electrode and the negative electrode and electrically insulate them, while increasing the permeability of ions such as lithium ions based on high porosity, thereby increasing ion conductivity. Commonly used separator substrates are porous polyolefin substrates made of polyolefin-based materials such as polyethylene (PE) and polypropylene (PP), which are advantageous in forming pores and have excellent chemical resistance, mechanical properties, and thermal properties. Summary of the invention

[0005] Technical issues

[0006] According to one aspect, the present disclosure provides a method for manufacturing a nonwoven separator for a lithium secondary battery, which has good heat shrinkage characteristics and exhibits low resistance and improved cycle performance when applied to a lithium secondary battery.

[0007] According to another aspect, the present disclosure provides a nonwoven separator for a lithium secondary battery exhibiting the above-mentioned characteristics.

[0008] According to still another aspect, the present disclosure provides a composite separator for a lithium secondary battery including the nonwoven separator having the above-mentioned properties.

[0009] According to still another aspect, the present disclosure provides an electrode assembly for a lithium secondary battery and a lithium secondary battery including the nonwoven separator having the above-mentioned characteristics.

[0010] Technical Solution

[0011] One aspect of the present disclosure provides a method for manufacturing a nonwoven separator for a lithium secondary battery according to the following embodiments.

[0012] A first embodiment relates to a method for producing a nonwoven separator for a lithium secondary battery,

[0013] The method comprises:

[0014] (S1) preparing a first solution in which β-chitin is dissolved in a first solvent and a second solution in which a poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) is dissolved in a second solvent;

[0015] (S2) performing coaxial electrospinning using the first solution as a core solution and the second solution as a shell solution to produce a nonwoven fabric formed of fibers having a core-shell structure having a core portion of β-chitin and a shell portion of a vinylidene fluoride-trifluoroethylene copolymer; and

[0016] (S3) heat-treating the nonwoven fabric at a temperature lower than the thermal decomposition point of β-chitin and higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer to melt and recrystallize the vinylidene fluoride-trifluoroethylene copolymer.

[0017] A second embodiment relates to a method for manufacturing a nonwoven separator for a lithium secondary battery according to the first embodiment,

[0018] The weight ratio of the core of β-chitin to the shell of the vinylidene fluoride-trifluoroethylene copolymer is about 50:50 to 99:1.

[0019] A third embodiment relates to a method for manufacturing a nonwoven separator for a lithium secondary battery according to the first embodiment or the second embodiment,

[0020] The first solvent is 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), and the second solvent is methyl ethyl ketone (MEK).

[0021] A fourth embodiment relates to a method for producing a nonwoven separator for a lithium secondary battery according to the first embodiment,

[0022] The temperature at which the nonwoven fabric is heat treated is about 150°C to 250°C.

[0023] A fifth embodiment relates to a method for producing a nonwoven separator for a lithium secondary battery according to the first embodiment,

[0024] The vinylidene fluoride-trifluoroethylene copolymer has crystals growing along a crystal axis, and the crystals growing along the crystal axis are oriented in a direction not parallel to the longitudinal direction of the fiber.

[0025] Another aspect of the present invention provides a nonwoven separator for a lithium secondary battery according to the following embodiments.

[0026] A sixth embodiment is directed to a nonwoven separator for a lithium secondary battery, comprising fibers having a core-shell structure having:

[0027] a core of β-chitin; and

[0028] The shell portion of the vinylidene fluoride-trifluoroethylene copolymer.

[0029] The vinylidene fluoride-trifluoroethylene copolymer has crystals grown along a crystal axis, and the crystals grown along the crystal axis are oriented in a direction that is not parallel to the longitudinal direction of the fiber.

[0030] A seventh embodiment relates to the nonwoven separator for a lithium secondary battery according to the sixth embodiment,

[0031] The crystals growing along the crystal axis are oriented in a direction substantially perpendicular to the longitudinal direction of the fiber.

[0032] An eighth embodiment relates to the nonwoven separator for a lithium secondary battery according to the sixth embodiment or the seventh embodiment,

[0033] The weight ratio of the core to the shell is about 50:50 to 99:1.

[0034] A ninth embodiment relates to the nonwoven separator for a lithium secondary battery according to any one of the sixth to eighth embodiments,

[0035] The average diameter of the fibers having a core-shell structure is about 200 nm to 2,000 nm.

[0036] A tenth embodiment relates to a separator for a lithium secondary battery according to any one of the sixth to ninth embodiments,

[0037] The nonwoven separator has a thickness of about 2 μm to 30 μm.

[0038] An eleventh embodiment relates to the separator for a lithium secondary battery according to any one of the sixth to tenth embodiments,

[0039] The basis weight of the nonwoven separator is about 2 g / m 2 Up to 10g / m 2 .

[0040] A twelfth embodiment relates to a separator for a lithium secondary battery according to any one of the sixth to eleventh embodiments,

[0041] The permeability of the nonwoven separator is about 50 sec / 100 cm3 or smaller.

[0042] A fourteenth embodiment relates to a separator for a lithium secondary battery according to any one of the sixth to twelfth embodiments,

[0043] It also includes a mixture of inorganic particles and a polymer coated on at least one surface of the nonwoven separator.

[0044] Still another aspect of the present disclosure provides a composite separator for a lithium secondary battery according to the following embodiments.

[0045] A fourteenth embodiment relates to a composite separator for a lithium secondary battery, comprising:

[0046] The nonwoven separator of any one of the sixth to thirteenth embodiments; and

[0047] A porous polymer film is laminated to at least one surface of the nonwoven separator.

[0048] Still another aspect of the present disclosure provides an electrode assembly for a lithium secondary battery according to the following embodiments.

[0049] A fifteenth embodiment relates to an electrode assembly for a lithium secondary battery, comprising:

[0050] a positive electrode; a negative electrode; and a separator disposed between the positive electrode and the negative electrode.

[0051] The separator is the nonwoven separator of any one of the sixth to thirteenth embodiments.

[0052] A sixteenth embodiment relates to an electrode assembly for a lithium secondary battery, comprising:

[0053] a positive electrode; a negative electrode; and a separator disposed between the positive electrode and the negative electrode.

[0054] The separator is the composite separator of the fourteenth embodiment.

[0055] Still another aspect of the present disclosure provides a lithium secondary battery according to the following embodiments.

[0056] A seventeenth embodiment is directed to a lithium secondary battery, comprising:

[0057] An electrode assembly according to a fifteenth embodiment.

[0058] An eighteenth embodiment relates to a lithium secondary battery, comprising:

[0059] An electrode assembly according to a sixteenth embodiment.

[0060] Beneficial Effects

[0061] According to the present disclosure, the nonwoven separator for lithium secondary battery includes a fiber with a core-shell structure, wherein the core-shell structure has a core of β-chitin and a shell of a vinylidene fluoride-trifluoroethylene copolymer. The vinylidene fluoride-trifluoroethylene copolymer has a crystal growing along a crystal axis. In addition, the crystal growing along the crystal axis is oriented in a direction not parallel to the longitudinal direction of the fiber.

[0062] β-chitin constituting the core of the fiber has excellent heat resistance and maintains the characteristics of the fiber even at high temperatures, which achieves good thermal shrinkage characteristics. In addition, β-chitin is a ferroelectric polymer that has ferroelectricity due to functional groups within the molecule, and therefore exhibits high affinity for lithium ions. Therefore, the fiber with a β-chitin core causes uniform migration of lithium ions and reduces resistance.

[0063] The vinylidene fluoride-trifluoroethylene copolymer constituting the shell of the fiber is also a ferroelectric polymer with beta-crystallinity. The shell of the vinylidene fluoride-trifluoroethylene copolymer formed on the surface of the core of beta-chitin by coaxial electrostatic spinning is melted and recrystallized by heat treatment to have crystals grown along the crystal axis, and the crystals grown along the crystal axis are oriented in a direction not parallel to the longitudinal direction of the fiber. The crystals grown along the crystal axis of the vinylidene fluoride-trifluoroethylene copolymer maximize ferroelectricity, especially when oriented in a direction substantially perpendicular to the longitudinal direction of the fiber. Therefore, the affinity of the nonwoven separator formed by the fiber of the core-shell structure disclosed in the present invention to lithium ions is further improved, so as to achieve low resistance and improved cycle performance when applied to lithium secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 is a surface SEM photograph of a nonwoven separator according to one embodiment of the present disclosure.

[0065] Figure 2 is a surface SEM photograph of a nonwoven separator according to a comparative example of the present disclosure.

[0066] Figure 3 GIWAXS analysis results of a nonwoven separator according to an embodiment of the present disclosure.

[0067] Throughout the several views of the drawings, corresponding reference numerals indicate corresponding components / assemblies. The drawings presented are illustrated for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of some elements in the drawings may be exaggerated relative to other elements to help improve understanding of the various embodiments. In addition, common but well-known elements that are useful or necessary in commercially feasible embodiments are generally not depicted to facilitate a less obstructive view of these various embodiments. DETAILED DESCRIPTION

[0068] In the following detailed description, reference is made to the accompanying drawings which form a part thereof. The illustrative embodiments described in the detailed description, drawings, and claims are not meant to be limiting. Other embodiments may be utilized, and other changes may be made without departing from the spirit or scope of the subject matter presented herein.

[0069] Throughout the specification, unless specifically described to the contrary, when it is mentioned that a part “includes” or “is provided with” a certain constituent element, it means that this does not exclude the constituent element, but includes or is further provided with other constituent elements.

[0070] As used herein, having a porous property means that an object includes a plurality of pores and gaseous and / or liquid fluids can flow from one side of the object to the other due to a structure in which the pores are connected to each other.

[0071] In this specification, the separator has a porous property including a large number of pores, and functions as a porous ion-conducting barrier that allows ions to pass while blocking electrical contact between a negative electrode and a positive electrode in an electrochemical device.

[0072] As used herein, "nonwoven fabric" means a fabric formed by entanglement of fibers with each other, rather than a fabric woven from warp yarns and weft yarns using a loom or a knitted fabric using a knitting machine.

[0073] As used herein, the term "substantially vertical direction" should be understood to include directions where the angle is exactly vertical (90°) as well as directions where the angle is 90°±15° (which are substantially vertical).

[0074] As used herein, the term "non-parallel directions" should be interpreted as including directions having angles of 20° to 90°.

[0075] As used herein, the words "about," "approximately," and "substantially" are used to mean a range or approximation of values ​​or degrees that take into account inherent manufacturing tolerances and material tolerances, and are used to prevent infringers from unfairly taking advantage of the present disclosure when precise or absolute values ​​are provided to aid in understanding the present disclosure.

[0076] In addition to the positive electrode, the negative electrode and the electrolyte, the separator is also one of the important elements of the lithium secondary battery. The separator plays a role in preventing the physical contact between the negative electrode and the positive electrode, and is closely related not only to the efficiency of the lithium secondary battery, but also to the safety of the lithium secondary battery.

[0077] Polyolefin-based separators are most widely used in lithium secondary batteries due to good chemical stability and mechanical strength. However, due to the material properties of porous polyolefin membranes and the manufacturing process, especially including stretching, separators may thermally shrink at high temperatures, resulting in melting of the polymer separator substrate and internal short circuits during thermal runaway. As a result, the risk of fire increases.

[0078] In this regard, a method of using a nonwoven fabric made of heat-resistant fibers such as polyethylene terephthalate as a separator substrate is proposed. The heat-resistant nonwoven fabric can be applied as a separator alone, or in a manner where a mixture of inorganic particles and a polymer is coated on the nonwoven fabric. Alternatively, the separator can be used in the form of a composite separator made by laminating and combining such a separator with a porous polymer film.

[0079] In the present disclosure, nanofibers having a core-shell structure of β-chitin and a copolymer (PVDF-TrFE) are prepared using coaxial electrospinning, and a nonwoven separator having maximized crystallinity is prepared by orienting the PVDF-TrFE polarization axis (b-axis) through appropriate heat treatment, and the nonwoven separator is applied to a lithium secondary battery. Then, as will be described below, it is determined that the resistance and battery cycle performance of the nonwoven separator are improved.

[0080] One embodiment of the present disclosure relates to a method for manufacturing a nonwoven separator for a lithium secondary battery, the method comprising:

[0081] (S1) preparing a first solution in which β-chitin is dissolved in a first solvent and a second solution in which a poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) is dissolved in a second solvent;

[0082] (S2) performing coaxial electrospinning using the first solution as a core solution and the second solution as a shell solution to produce a nonwoven fabric formed of fibers having a core-shell structure having a core portion of β-chitin and a shell portion of a vinylidene fluoride-trifluoroethylene copolymer; and

[0083] (S3) heat-treating the nonwoven fabric at a temperature lower than the thermal decomposition point of β-chitin and higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer to melt and recrystallize the vinylidene fluoride-trifluoroethylene copolymer.

[0084] First, a first solution in which β-chitin is dissolved in a first solvent and a second solution in which a vinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) is dissolved in a second solvent are prepared respectively (S1).

[0085] The first solvent for dissolving β-chitin is not limited, but may be any solvent capable of dissolving β-chitin for electrospinning, such as 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP).

[0086] The second solvent for dissolving the PVDF-TrFE is not limited, but may be any solvent capable of dissolving the PVDF-TrFE for electrospinning, such as, for example, methyl ethyl ketone (MEK).

[0087] Subsequently, the first solution as a core solution and the second solution as a shell solution were subjected to coaxial electrospinning to produce a nonwoven fabric formed of fibers having a core-shell structure having a core portion of β-chitin and a shell portion of a vinylidene fluoride-trifluoroethylene copolymer (S2).

[0088] As is known, by utilizing a coaxial electrospinning machine, a first solution of β-chitin dissolved in a first solvent is supplied as a core solution, and a second solution of vinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) dissolved in a second solvent is supplied as a shell solution, and electrospinning is performed via a nozzle. Then, a nonwoven fabric formed by fibers having a core-shell structure can be prepared, wherein the core-shell structure has a core of β-chitin and a shell of vinylidene fluoride-trifluoroethylene copolymer.

[0089] According to one embodiment, the production of nonwoven fabrics by electrospinning is carried out as follows: using a first solution of β-chitin and a second solution of vinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) as a core solution and a shell solution, respectively, the first solution and the second solution are introduced into a coaxial electrospinning nozzle adjusted to a temperature of about 80 ° C at room temperature, and electrospinning is performed with an electric field formed between the electrospinning nozzle and the substrate. The electric field can be formed by applying a voltage of, for example, 1kV to 30kV. Then, the first solution and the second solution are spun from the coaxial electrospinning nozzle to which a high voltage is applied and coated on the substrate in the form of fibers to form a nonwoven fabric. The formed nonwoven fabric can be peeled off from the substrate and used as a separator, or when another separator or electrode is used as a substrate, the nonwoven fabric can be used in the form of a coating on the substrate.

[0090] Most solvents can be dried immediately after electrospinning, but the solvent can also be completely removed using a separate drying device.

[0091] At this time, the substrate, which is the target of the coaxial electrospinning opposite to the spinning nozzle, may be positioned in a direction parallel to the floor or perpendicular to the floor.

[0092] Subsequently, the nonwoven fabric is heat-treated at a temperature lower than the thermal decomposition point of β-chitin and higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer to melt and recrystallize the vinylidene fluoride-trifluoroethylene copolymer (S3). Since the melting point of the vinylidene fluoride-trifluoroethylene copolymer is about 146°C, the heat treatment temperature can be, for example, about 150°C to 250°C, but is not limited thereto.

[0093] The nonwoven separator thus prepared is formed by the fiber with a core-shell structure, wherein the core-shell structure has a core of β-chitin and a shell of a vinylidene fluoride-trifluoroethylene copolymer, and the vinylidene fluoride-trifluoroethylene copolymer has a crystal growing along a crystal axis. In addition, the crystal growing along the crystal axis is oriented in a direction not parallel to the longitudinal direction of the fiber.

[0094] β-chitin constituting the core of the fiber has excellent heat resistance and maintains the characteristics of the fiber even at high temperatures, which achieves good thermal shrinkage characteristics. In addition, β-chitin is a ferroelectric polymer that has ferroelectricity due to functional groups within the molecule, and therefore exhibits high affinity for lithium ions. Therefore, the fiber with a β-chitin core causes uniform migration of lithium ions and reduces resistance.

[0095] The vinylidene fluoride-trifluoroethylene copolymer constituting the shell of the fiber is also a ferroelectric polymer with β crystallinity. The shell of the vinylidene fluoride-trifluoroethylene copolymer formed on the surface of the core of β-chitin by coaxial electrostatic spinning is melted and recrystallized by heat treatment, and has a crystal (epitaxial growth) grown along the crystal axis. The epitaxial growth along the crystal axis of the vinylidene fluoride-trifluoroethylene copolymer is also observed on the surface of polytetrafluoroethylene or graphene, but the b-axis (polarization axis) is parallel to the crystal of polytetrafluoroethylene or graphene, which limits the ferroelectricity of the vinylidene fluoride-trifluoroethylene copolymer. The crystal grown along the crystal axis of the vinylidene fluoride-trifluoroethylene copolymer maximizes ferroelectricity, especially when oriented in a direction substantially perpendicular to the longitudinal direction of the fiber. Therefore, the affinity of the non-woven separator formed by the fiber of the core-shell structure of the present disclosure to lithium ions is further increased, so as to achieve low resistance and improved cycle performance when applied to lithium secondary batteries. In addition, problems such as lithium dendrite precipitation can be suppressed and eliminated in some cases.

[0096] At this time, a weight ratio of the core of β-chitin to the shell of the vinylidene fluoride-trifluoroethylene copolymer constituting the fiber of the nonwoven fabric may be about 50:50 to 99:1, for example, about 50:50 to 80:20, but is not limited thereto.

[0097] The average diameter of the fiber of core-shell structure can be adjusted according to the concentration of core solution and shell solution and the diameter of spinning nozzle. For example, the average diameter of the fiber of core-shell structure can be 200nm to 2,000nm, or 300nm to 1000nm. The nonwoven fabric formed by the fiber of core-shell structure is mutually entangled and has a three-dimensional (3D) shape, and the pore size of the nonwoven fabric can be adjusted according to the average diameter of the fiber of core-shell structure and the loading amount of the fiber. The basis weight of the nonwoven fabric can be 2-10g / m 2 Up to 10g / m 2 , but not limited thereto. The permeability of the nonwoven fabric may be about 50 seconds / 100 cm 3 or smaller, but not limited thereto.

[0098] The thickness of the nonwoven fabric may be about 2 μm to 30 μm, but is not limited thereto, and the nonwoven fabric formed by electrostatic spinning is easily thinned.

[0099] The prepared nonwoven separator may also include a mixture of inorganic particles and a polymer coated on at least one surface of the nonwoven fabric.

[0100] The inorganic particles are not particularly limited as long as they are electrochemically stable. For example, the inorganic particles are not particularly limited as long as they are within the operating voltage range of the lithium secondary battery used (for example, based on Li / Li + In particular, the use of inorganic particles with a high dielectric constant can contribute to the increase in the dissociation of electrolyte salts such as lithium salts in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte.

[0101] For the above reasons, the inorganic particles may include high dielectric constant inorganic particles having a dielectric constant of 5 or more, or 10 or more. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include any one selected from the group consisting of BaTiO3, Pb(Zr x ,Ti 1-x )O3(PZT, where 0 <x<1)、Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0 <x<1,0<y<1)、(1-x)Pb(Mg 1 / 3 Nb 2 / 3 ) 3-xPbTiO3 (PMN-PT, where 0 < x < 1), hafnium oxide (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite, AlOOH, SiC, and TiO2, or a mixture of two or more thereof.

[0102] In addition, inorganic particles having lithium ion transfer ability (i.e., inorganic particles containing elemental lithium but not storing lithium and having the ability to transfer lithium ions) can be used as the inorganic particles. Non-limiting examples of inorganic particles having lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), such as 14Li2O-9Al2O3-38TiO2-39P2O5 (LiAlTiP) x O y series glasses (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), such as Li 3.25 Ge 0.25 P 0.75 S4 of lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, w < 5), such as lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), such as SiS2 series glasses (Li x Si y S z of Li3PO4-Li2S-SiS2 (Li x P y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), and such as P2S5 series glasses (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), or a mixture of two or more thereof.

[0103] Inorganic particles can be mixed with polymer and coated on at least one surface of nonwoven fabric. The limiting examples of polymer include polyvinylidene fluoride, polyvinylidene fluoride-copolymerization-hexafluoropropylene, polyvinylidene fluoride-copolymerization-trichloroethylene, polyvinylidene fluoride-copolymerization-chlorotrifluoroethylene and polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer (polyethylene-copolymerization-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide or a mixture of both or more thereof. Both ion-conducting polymer and non-ion-conducting polymer can be used.

[0104] The mixture of inorganic particles and polymer can be applied by further dispersing the inorganic particles in a slurry in which the polymer is dissolved or dispersed in a solvent, and then applying it on at least one surface of the nonwoven fabric and drying. By this coating, according to the pore size of the nonwoven fabric, the mixture of inorganic particles and polymer can be positioned only on the surface of the nonwoven fabric, positioned on both the surface and the inner hole of the nonwoven fabric, or mainly positioned inside the porous polymer nonwoven fabric.

[0105] In addition to the inorganic particles between the fibers, the inorganic particles can be positioned to substantially contact each other. In this case, when the mixed polymer is formed as a coating on a part or all of the surface of the inorganic particles, the polymer can connect and fix the inorganic particles so that the inorganic particles remain combined with each other.

[0106] The above-mentioned type of nonwoven separator may be laminated on at least one surface of a porous polymer film and used in the form of a composite separator.

[0107] The porous polymer membrane may be simply laminated to the nonwoven separator or attached to the nonwoven separator by a process such as lamination.

[0108] The porous polymer film can be, for example, a polyolefin porous polymer film. Any polyolefin porous polymer film commonly used as a separator can be used. Examples thereof include polyethylene such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene, and ultra-high molecular weight polyethylene, and polyolefin-based polymers such as polypropylene, polybutylene, and polypentene, which can be used alone or in a mixture of two or more thereof to form a polymer. When such a polyolefin porous polymer film is laminated with a nonwoven separator and used as a composite separator, the polyolefin porous polymer film exhibits a shutoff function at a temperature of, for example, 80° C. to 150° C. In this aspect, the polyolefin porous polymer film can be made of polyethylene.

[0109] The above nonwoven separator or composite nonwoven separator may be interposed between a positive electrode and a negative electrode and used as an electrode assembly for a lithium secondary battery.

[0110] Hereinafter, a positive electrode and a negative electrode constituting an electrode assembly will be described by way of example.

[0111] The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.

[0112] In the positive electrode, the positive electrode collector is not particularly limited as long as it is conductive and does not cause chemical changes in the battery, and examples thereof include stainless steel; aluminum; nickel; titanium; calcined carbon; or aluminum or stainless steel subjected to carbon, nickel, titanium or silver surface treatment. In addition, the thickness of the positive electrode collector can typically be about 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode collector to improve the adhesion to the positive electrode active material. For example, the positive electrode collector can be used in various forms (such as films, sheets, foils, nets, porous bodies, foams, non-woven bodies, etc.).

[0113] The positive electrode active material layer may include a known positive electrode active material, a conductive material, and a binder.

[0114] Positive electrode active materials include: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metal elements; lithium manganese oxides such as Li 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x is 0.01 to 0.3); 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and x is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4, wherein some of the Li in the formula is replaced by alkaline earth metal ions; disulfide compounds; Fe2(MoO4)3, but not limited thereto.

[0115] The conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as it has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples thereof include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, which can be used alone or as a mixture of two or more thereof. Based on the total weight of the positive electrode active material layer, the conductive material can typically be included in an amount of about 1% by weight to 30% by weight.

[0116] Binder is used to enhance the adhesion between positive active material particles and the adhesion between positive active material and positive current collector. Its specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-copolymer-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluorinated rubber or its various copolymers. These can be used alone or in a mixture of two or more thereof. Based on the gross weight of the positive active material layer, the binder can be included in an amount of about 1 weight % to 30 weight %.

[0117] The positive electrode can be manufactured according to a conventional positive electrode manufacturing method. For example, the positive electrode can be manufactured by applying a composition for forming a positive electrode active material layer comprising a positive electrode active material and optionally a binder and a conductive material to a positive electrode current collector, followed by drying and rolling. At this time, the types and contents of the positive electrode active material, the binder and the conductive material are as described above.

[0118] The solvent may be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, which may be used alone or as a mixture of two or more thereof. Considering the applied thickness and manufacturing yield of the slurry, the amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, the conductive material and the binder, and provide a viscosity that can show good thickness uniformity when subsequently applied to positive electrode production.

[0119] Alternatively, the positive electrode may be manufactured by casting the composition for forming the positive electrode active material layer on a separate support, and then laminating a film obtained by peeling from the support on a positive electrode current collector.

[0120] The negative electrode includes a negative electrode current collector and a negative electrode active material layer positioned on the negative electrode current collector.

[0121] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and examples thereof include copper; stainless steel; aluminum; nickel; titanium; calcined carbon; copper or stainless steel subjected to carbon, nickel, titanium or silver surface treatment; and aluminum-cadmium alloy. In addition, the thickness of the negative electrode current collector may typically be about 3 μm to 500 μm, and like the positive electrode current collector, fine irregularities may be formed on the surface of the negative electrode current collector to enhance the binding force to the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, nonwovens, etc.

[0122] The negative electrode active material layer optionally contains a binder and a conductive material in addition to the negative electrode active material. The negative electrode active material layer can be prepared, for example, by applying a negative electrode forming composition containing a negative electrode active material and optionally a binder and a conductive material to a negative electrode current collector and drying the negative electrode forming composition, or by casting the negative electrode forming composition onto a separate support and then laminating the film obtained by peeling off the support onto the negative electrode current collector.

[0123] The negative electrode active material may be any compound capable of reversibly intercalating and deintercalating lithium. Examples include carbon-based materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO2, vanadium oxide, lithium vanadium oxide; or a composite material comprising the above metal compound and a carbon-based material, such as a Si-C composite material or a Sn-C composite material, and these can be used alone or as a mixture of two or more thereof. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural or artificial graphite, crystalline graphite (Kish graphite), pyrolytic carbon, carbon fiber based on mesophase pitch, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbon such as coke derived from petroleum or coal tar pitch.

[0124] The binder and conductive material may be the same as those previously described for the positive electrode.

[0125] Meanwhile, a lithium secondary battery according to one aspect of the present disclosure includes the above-mentioned electrode structure.

[0126] The lithium secondary battery includes the above-mentioned electrode structure and an electrolyte. Examples of the electrolyte used in the present disclosure include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes and melt inorganic electrolytes that can be used to produce lithium secondary batteries, but are not limited thereto.

[0127] For example, the electrolyte may include an organic solvent and a lithium salt.

[0128] The organic solvent can be used without particular limitation, as long as it can be used as a medium for ion migration involved in the electrochemical reaction of the battery. Specific examples of organic solvents include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether-based solvents such as dibutyl ether and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; and sulfolane. Wherein, according to one embodiment, a carbonate-based solvent can be used, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery and a linear carbonate-based compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) with low viscosity can be used. In this case, excellent electrolyte performance can be obtained by mixing cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9.

[0129] The lithium salt can be any compound that can provide the lithium ions used in the lithium secondary battery without particular limitation. Examples of lithium salts include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI and LiB(C2O4)2. The concentration of the lithium salt can be used in the range of about 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, which can show good electrolyte performance and can effectively transport lithium ions.

[0130] For the purpose of improving the life characteristics of the battery, suppressing the reduction of the battery capacity, and improving the discharge capacity of the battery, in addition to the above electrolyte components, the electrolyte may further contain one or more additives, for example, a halogenated alkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, N-glyme dimethyl ether, hexanetriamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum chloride. In this case, the additive may be included in an amount of about 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0131] The lithium secondary battery according to the present disclosure may be used in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0132] Hereinafter, the embodiments of the present disclosure will be described in detail so that those skilled in the art can easily implement the present disclosure. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein.

[0133] Embodiment 1:

[0134] The first solution was prepared by dissolving β-chitin (Glycosyn, β-chitin) at a concentration of 0.6 wt% in HFIP (1,1,1,3,3,3-hexafluoro-2-propanol). In addition, the second solution was prepared by dissolving vinylidene fluoride-trifluoroethylene copolymer (Solvay, VDF / TrFE=75mol%:25mol%) in MEK (methyl ethyl ketone) at a concentration of 10 wt%.

[0135] The prepared first solution and second solution, which were used as a core solution and a shell solution, respectively, were introduced into a coaxial electrospinning nozzle controlled at a temperature of 25° C., and dried while randomly performing electrospinning by applying a voltage of 1.5 kV between the electrospinning nozzle and a support made of SUS foil to prepare a nonwoven fabric formed of fibers having a core-shell structure having a core portion of β-chitin and a shell portion of a vinylidene fluoride-trifluoroethylene copolymer.

[0136] Subsequently, the nonwoven fabric was heat treated at 200° C. for 30 minutes and then left at room temperature to obtain a nonwoven separator. In the nonwoven separator, the weight ratio of the core of β-chitin to the shell of the vinylidene fluoride-trifluoroethylene copolymer was 70:30.

[0137] Embodiment 2:

[0138] A nonwoven separator was prepared in the same manner as in Example 1, except that the average diameter of the fibers was changed under the conditions listed in Table 1.

[0139] Comparative Example 1:

[0140] Instead of coaxial electrospinning, electrospinning was performed with β-chitin alone under the conditions listed in Table 1 .

[0141] Comparative Example 2:

[0142] Instead of coaxial electrospinning, electrospinning was performed using only the vinylidene fluoride-trifluoroethylene copolymer under the conditions listed in Table 1 .

[0143] Comparative Example 3:

[0144] A nonwoven fabric separator was prepared by immersing the nonwoven fabric prepared according to Comparative Example 1 in a solution in which a vinylidene fluoride-trifluoroethylene copolymer was dissolved in methyl ethyl ketone (MEK) at a concentration of 10 wt %, followed by drying.

[0145] Comparative Example 4:

[0146] A nonwoven separator was prepared in the same manner as in Example 1, except that the nonwoven fabric prepared by coaxial electrospinning was not heat-treated.

[0147] Comparative Example 5:

[0148] A nonwoven separator was prepared in the same manner as in Example 1, except that the nonwoven fabric prepared by coaxial electrospinning was heat-treated at 120° C. for 1 hour and then left at room temperature.

[0149] <Average fiber diameter>

[0150] In this specification, the average diameter of the fibers is defined as measured as follows.

[0151] Carbon tape is used to fix nonwoven separator sample to the slide for SEM measurement.Then, ion sputtering is used to carry out Pt coating 60 seconds to the surface.Use FE-SEM (Hitachi S-4800) equipment to measure the sample coated with Pt under 10kV condition.Use software, in the x500 image observed with FE-SEM, more than 10 points measure the diameter of a fiber strand, and by the value of measurement is averaged to calculate fiber diameter.

[0152] <Basis Weight of Nonwoven Fabric>

[0153] In this specification, the basis weight of a nonwoven fabric is defined as measured as follows.

[0154] The basis weight of the nonwoven fabric is measured as per 1 m 2 the weight of the manufactured nonwoven fabric.

[0155] <Permeability of the nonwoven separator>

[0156] In this specification, the permeability of the nonwoven separator is defined as measured as follows.

[0157] Measure the permeability of the separator according to JIS P8117.

[0158] <Measurement of thermal shrinkage rate>

[0159] Place the prepared nonwoven separator in an oven maintained at 150 °C for 30 minutes, then take it out, and evaluate the thermal shrinkage rate by measuring the lengths in the machine direction (MD) and the transverse direction (TD) before and after being placed in the oven.

[0160] <Measurement of ER and cycle performance>

[0161] Cut each nonwoven separator according to the examples and comparative examples and place it in a Hoshen 2016 coin cell. Then, when impregnating the nonwoven separator with the electrolyte, measure the resistance value by the alternating current method using a 1M LiPF6 - ethylene carbonate / ethyl methyl carbonate (weight ratio 3:7) electrolyte at 25 °C by electrochemical impedance spectroscopy (EIS).

[0162] In addition, charge and discharge are repeated at a rate of 1C at 25 °C in the range of 2.5 V to 4.25 V, and the cycle performance (capacity retention rate) is measured by calculating the ratio of the initial discharge capacity to the discharge capacity after 200 cycles.

[0163] Table 1

[0164]

[0165]

[0166] As shown in Table 1, it can be seen that when applied to lithium secondary batteries, the nonwoven separators of Examples 1 and 2 exhibit excellent thermal shrinkage characteristics, while showing improved resistance and cycle characteristics. For example, for Examples 1 and 2, under MD / TD, the thermal shrinkage rate is 0 / 0%, and the cycle performances are 98% and 99% respectively, showing excellent characteristics compared with the comparative examples.

[0167] Meanwhile, the nonwoven separator of Comparative Example 1 formed of β-chitin fibers has: a resistance characteristic of 0.64Ω, which is higher than that of the nonwoven separators of Examples 1 and 2; and a cycle performance of 80%, which is lower than that of the nonwoven separators of Examples 1 and 2. The nonwoven separator of Comparative Example 2 formed of a vinylidene fluoride-trifluoroethylene copolymer has a heat shrinkage rate of 28 / 27%, which has poor heat resistance and poor high-temperature heat shrinkage characteristics.

[0168] The nonwoven separator of Comparative Example 3 in which a vinylidene fluoride-trifluoroethylene copolymer is applied to a β-chitin nonwoven fabric by an impregnation method has a poor resistance characteristic with a resistance value of 0.71Ω, and the nonwoven separator of Comparative Example 4 in which no post-heat treatment process is performed has: a resistance characteristic of 0.55Ω, which is higher than that of the nonwoven separators of Examples 1 and 2; and a cycle performance of 84%, which is lower than that of the nonwoven separators of Examples 1 and 2.

[0169] The nonwoven separator of Comparative Example 5, which was heat-treated at a temperature lower than the melting point of the vinylidene fluoride-trifluoroethylene copolymer, had: a resistivity characteristic of 0.41Ω, which was higher than that of the nonwoven separators of Examples 1 and 2; and a cycle performance of 95%, which was lower than that of the nonwoven separators of Examples 1 and 2.

[0170] Meanwhile, in Example 2 in which the average diameter of the fibers was about 500 nm, the resistance was about 0.32Ω, which was lower than the resistance of about 0.37Ω in Example 1 in which the average diameter of the fibers was about 700 nm.

[0171] Figure 1 is a surface SEM photograph of the nonwoven separator according to Example 1 of the present disclosure, Figure 2 is a surface SEM photograph of the nonwoven separator according to Comparative Example 5 of the present disclosure, and Figure 3 GIWAXS analysis of the nonwoven separator according to Example 1 of the present disclosure.

[0172] Reference Figure 1 and Figure 2 , it can be seen that Figure 2 Compared with the nonwoven separator according to Comparative Example 5, Figure 1 The nonwoven separator according to Example 1 exhibits a smoother surface. For example, it can be seen that the surface of the nonwoven separator to which the present disclosure is applied is formed to be smoother.

[0173] Figure 3 Graph depicting the results of grazing-incidence wide-angle X-ray scattering (GIWAXS) analysis of the nonwoven separator according to Example 1 of the present disclosure. Figure 3 , it can be seen that due to the heat treatment at a temperature higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer, the vinylidene fluoride-trifluoroethylene copolymer undergoes a melting-recrystallization process, thereby generating a (200) peak at the equatorial position and a (110) peak at a point 30° away from the meridian position. That is, it can be seen that when the (200) peak is at the equatorial position, the a-axis is oriented parallel to the surface of the substrate, and when the (110) peak is located 30° away from the position, the b-axis is perpendicular to the substrate, thereby generating a crystalline phase having a b-axis oriented perpendicular to the substrate.

[0174] As a result, it can be determined that the b-axis of the PVDF-TrFE is oriented substantially perpendicularly to the longitudinal direction of the fiber, which maximizes the ferroelectricity of the nonwoven separator of the present disclosure.

[0175] It will be understood from the foregoing that for the purpose of illustration, multiple embodiments of the present disclosure are described herein, and various modifications may be made without departing from the scope and spirit of the present disclosure. Therefore, multiple embodiments disclosed herein are not intended to be limiting, with the true scope and spirit being indicated by the appended claims.

Claims

1. A method for producing a nonwoven separator for a lithium secondary battery, the method comprising: (S1) preparing a first solution in which β-chitin is dissolved in a first solvent and a second solution in which a poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) is dissolved in a second solvent; (S2) performing coaxial electrospinning using the first solution as a core solution and the second solution as a shell solution to produce a nonwoven fabric formed of fibers having a core-shell structure having a core portion of the β-chitin and a shell portion of the vinylidene fluoride-trifluoroethylene copolymer; and (S3) heat-treating the nonwoven fabric at a temperature lower than the thermal decomposition point of the β-chitin and higher than the melting point of the vinylidene fluoride-trifluoroethylene copolymer to melt and recrystallize the vinylidene fluoride-trifluoroethylene copolymer. 2 . The method according to claim 1 , wherein a weight ratio of the core of the β-chitin to the shell of the vinylidene fluoride-trifluoroethylene copolymer is about 50:50 to 99:

1.

3. The method of claim 1, wherein the first solvent is 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), and the second solvent is methyl ethyl ketone (MEK).

4. The method according to claim 1, wherein the temperature at which the nonwoven fabric is heat-treated is about 150°C to 250°C. 5 . The method according to claim 1 , wherein the vinylidene fluoride-trifluoroethylene copolymer has crystals grown along a crystal axis, and the crystals grown along the crystal axis are oriented in a direction that is not parallel to a longitudinal direction of the fiber.

6. A nonwoven separator for a lithium secondary battery, comprising: A fiber having a core-shell structure having a core portion of β-chitin and a shell portion of a vinylidene fluoride-trifluoroethylene copolymer, The vinylidene fluoride-trifluoroethylene copolymer has crystals growing along a crystal axis, and the crystals growing along the crystal axis are oriented in a direction not parallel to a longitudinal direction of the fiber.

7. The nonwoven separator according to claim 6, wherein the crystals grown along the crystal axis are oriented in a direction substantially perpendicular to the longitudinal direction of the fibers.

8. The nonwoven separator of claim 6, wherein the weight ratio of the core to the shell is about 50:50 to 99:

1. 9 . The nonwoven separator according to claim 6 , wherein the average diameter of the fiber having a core-shell structure is about 200 nm to 2,000 nm. 10 . The nonwoven separator according to claim 6 , wherein the thickness of the nonwoven separator is about 2 μm to 30 μm.

11. The nonwoven separator of claim 6, wherein the basis weight of the nonwoven separator is about 2 g / m 2 Up to 10g / m 2 .

12. The nonwoven separator according to claim 6, wherein the permeability of the nonwoven separator is about 50 seconds / 100 cm 3 or smaller.

13. The nonwoven separator according to claim 6, further comprising a mixture of inorganic particles and a polymer coated on at least one surface of the nonwoven separator.

14. A composite separator for a lithium secondary battery, comprising: The nonwoven separator according to any one of claims 6 to 13; and A porous polymer film is laminated on at least one surface of the nonwoven separator.

15. An electrode assembly for a lithium secondary battery, comprising: positive electrode; negative electrode; and A separator disposed between the positive electrode and the negative electrode, The separator is a nonwoven separator according to any one of claims 6 to 13.

16. An electrode assembly for a lithium secondary battery, comprising: positive electrode; negative electrode; and A separator disposed between the positive electrode and the negative electrode, The separator is a composite separator according to claim 14. 17 . A lithium secondary battery comprising the electrode assembly according to claim 15 .

18. A lithium secondary battery comprising the electrode assembly according to claim 16.